Systematic treatment and prevention of cardiac digoxin toxicity - Alshaer, Omar Rezk; Binobaid, Abdullah Obaid; Mofti, Abdelelah Hesham; Sadagah, Mohannad Mahmood; Olwi, Khalid Mustafa; Alsulaiman, Abdullah Saad; Zabidi, Ahmed Hatem; Ghabashi, Feras Ayman; Ibrahim, Mohammad Abdullah; Bamberook, Abdulaziz Mohammed; Jan, Abdulla Abid (International Journal Of Community Medicine And Public Health, 2021)
Digoxin has a narrow therapeutic index, such as complicated pharmacokinetics and dynamics. Many drug interactions may occur when the administration of one drug alters the clinical effects of another. As a result, digoxin toxicity can be a common condition within clinical settings that might lead to the development of many morbidities and even mortality. Many studies were published to investigate the efficacy and safety of different management modalities to enhance the outcomes that follow digoxin administration. The aim of the study was to discuss the approaches to systematically treat and prevent the development of cardiac digoxin toxicity. The findings are based on evidence from previous studies in the literature. To be specific, Fab fragments are the most effective modalities that can be used to treat severe cases within ideal periods. However, evidence regarding their administration for asymptomatic or mild cases is still poor regarding the cost-efficacy and the development of serious adverse events. Physicians should primarily care for a better intervention as it is usually associated with a significantly more enhanced prognosis and clinical outcomes. Nevertheless, adequate monitoring of the patients and evaluation of their personal and medical history are important steps in the process, and further approaches are still needed. Also, detailed information about our intended outcomes is furtherly discussed within the manuscript.